2018
DOI: 10.1071/hc17074
|View full text |Cite
|
Sign up to set email alerts
|

Effect of multimorbidity on health service utilisation and health care experiences

Abstract: INTRODUCTION: Multimorbidity, the co-existence of two or more long-term conditions, is associated with poor quality of life, high health care costs and contributes to ethnic health inequality in New Zealand (NZ). Health care delivery remains largely focused on management of single diseases, creating major challenges for patients and clinicians. AIM:To understand the experiences of people with multimorbidity in the NZ health care system. METHODS:A questionnaire was sent to 758 people with multimorbidity from tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 33 publications
1
32
0
1
Order By: Relevance
“…Current treatment guidelines overwhelmingly focus on a single disease and the health system is fragmented and sub-specialised [ 64 ]. Poor patient-provider communication, limited standard consultation time, lack of care coordination and shared decision-making are important challenges for managing multimorbidity [ 65 , 66 ]. These challenges are even more marked for Aboriginal people who often fail to receive safe and culturally appropriate health services, and may be exposed to institutional racism, poor communication with health providers and economic hardship [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Current treatment guidelines overwhelmingly focus on a single disease and the health system is fragmented and sub-specialised [ 64 ]. Poor patient-provider communication, limited standard consultation time, lack of care coordination and shared decision-making are important challenges for managing multimorbidity [ 65 , 66 ]. These challenges are even more marked for Aboriginal people who often fail to receive safe and culturally appropriate health services, and may be exposed to institutional racism, poor communication with health providers and economic hardship [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, patients with multimorbidity face increasingly complicated medical lifestyle with fragmented appointments, investigations, polypharmacy, and medical regimes. 6 Also, patients with multimorbidity are experiencing difficulties with access to information, 7,8 lack of coherence or coordination in treatments 8,9 and managing and adhering to treatment recommendation. 8,10 Acute medical illness in older adults is associated with several adverse outcomes [11][12][13][14][15] and the majority of the acutely hospitalized older medical patients are multimorbid.…”
Section: Introductionmentioning
confidence: 99%
“…Haverhals et al [17] found that patients with multimorbidity often felt their primary care physician was too busy to answer their medication questions. This is likely to be similar in New Zealand, where patients with multimorbidity frequently report having too much to discuss in one primary care appointment [27]. Pharmacists could potentially provide key information and answer medication questions; however, in other studies, many patients report never or rarely receiving advice from their pharmacist [28] and in a New Zealand study only a small proportion of patients reported using their pharmacist as a primary source of medication information [29].…”
Section: Discussionmentioning
confidence: 93%